Gender norms and differences in access and use of climate-smart agricultural technology in Burundi - Nchanji, Eileen Bogweh; Lutomia, Cosmas Kweyu (2024)
The study aimed to explore gender dynamics in access to and use of climate-smart agricultural (CSA) technologies among smallholder bean farmers in Burundi. The scope covered communes in Kirundo and Muyinga provinces, focusing on identifying gender gaps in CSA adoption. The data included quantitative information on household characteristics, bean production, access to CSA interventions, and decision-making processes. The Principal Investigators sought to understand how CSA adoption impacts gender norms and equality, addressing questions about the influence of joint decision-making, access to information, and group participation on closing gender gaps​.